2017
DOI: 10.3390/fermentation3040062
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of a Distilled Alcoholic Beverage Obtained by Fermentation of Banana Waste (Musa cavendishii) from Selected Yeast

Abstract: Banana is one of the most important fruits in the Brazilian diet and is mainly consumed naturally. Losses from crop to final consumer are high and estimated in about 30%. The aim of this work was to elaborate a distilled alcoholic beverage from discarded banana and to compare with commercial trademarks. Initially, yeast strains were isolated from banana fruit and characterized by their production of volatile aroma compounds. The highest aroma-producing yeast isolate was identified by ITS-rRNA gene sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Some compounds present in the distilled spirits produced in this study (ethyl acetate, 3-methyl-1-butanol, ethyl decanoate, and 1-decanol) were also found in rum and distilled spirits from other study [ 32 ]. These commonly found aromas provide a sensory quality to the product.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Some compounds present in the distilled spirits produced in this study (ethyl acetate, 3-methyl-1-butanol, ethyl decanoate, and 1-decanol) were also found in rum and distilled spirits from other study [ 32 ]. These commonly found aromas provide a sensory quality to the product.…”
Section: Resultssupporting
confidence: 64%
“…These commonly found aromas provide a sensory quality to the product. Comparing the VOCs (Table 2 ) identified in sweet potato distillates (LPB1-93, CA-11, and ATCC 26,602) with those of the banana spirit (BS) produced by Matos et al [ 32 ], it was verified that the production of sweet potato distilled spirit is feasible, as it presents characteristic flavors also present in distilled spirits produced from other raw materials such as sugarcane. Many chemical transformations and compounds produced, such as aldehydes, acids, and esters, are related to the maturation and aging process of the distillates.…”
Section: Resultsmentioning
confidence: 86%
“…Considering the BPP of the mixed substrate and the mixing ratio of 4:1 (PW:BW), this suggests a BW-BPP of 476 L N •(kg VSS) −1 . The lower BPP of BW is attributed to its lower share of carbohydrates compared to PW [27,44,48,50,52,53]. Specifically, the pineapple core is rich in sugar [61].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated specific and peculiar features of non-conventional yeasts in winemaking and their interactions with Saccharomyces cerevisiae, the main actor of fermentation [1][2][3][4][5]. Other reports focus on the microbiota of specific ecological niches, such as sherry wines [6], malting and brewing environments [7], and banana wastes [8]. Selected indigenous S. cerevisiae strains coming from Piceno DOC wines were also investigated by Agarbati et al [9], while Capece et al [10] reviewed recent developments on the use of conventional and non-conventional yeast in beer production.…”
mentioning
confidence: 99%